Analisis Pengelolaan Limbah Medis Padat di Rumah Sakit Umum Daerah Haji Abdoel Madjid Batoe (RSUD HAMBA) Kabupaten Batanghari - Nasrul, Nasrul; Ilham, Ilham; Suryono, Suryono (Universitas Batanghari Jambi, 2024)
Regional General Hospital Haji Abdoel Madjid Batoe (RSUD HAMBA) Batanghari Regency is included in the ten hospitals that produce the most solid medical waste in 2021. In 2022, 115,781 kg of waste is generated, consisting of 14,425 kg of infectious solid waste and 14,425 kg of non-infectious waste 101.356 kgs. If the increase in medical waste is not addressed and managed seriously, it will cause massive environmental degradation. The purpose of this research is to analyze the management of solid medical waste (Sorting and Container, Transportation, Storage and Processing) and develop a solid medical waste management strategy at HAMBA Hospital in Batanghari Regency according to Minister of Environment and Forestry Regulation P.56/Menlhk-Setjen/2015. The process of sorting and container has been separated directly from the waste producer, transportation and storage are transported by special officers (Cleaning Service) and stored in the temporary storage area (TPS) of B3 waste. Processing using its own incinerator which already has a permit. The strategy for managing solid medical waste at HAMBA Hospital in Batanghari Regency with a SWOT analysis, namely, establishing cooperation with other hospitals and health centers, providing education and training budgets for management officers and operators to obtain B3 waste management competency certification.